Individual and Organizational Antecedents of Misconduct in Organizations - Andreoli, Nicole (Journal of business ethics, 2008)
A heterogeneous survey sample of for-profit, non-profit and government employees revealed that organizational factors but not personal characteristics were significant antecedents of misconduct and job satisfaction. Formal organizational compliance practices and ethical climate were independent predictors of misconduct, and compliance practices also moderated the relationship between ethical climate and misconduct, as well as between pressure to compromise ethical standards and misconduct. Misconduct was not predicted by level of moral reasoning, age, sex, ethnicity, job status, or size and type of organization. Demographic variables predicted job satisfaction and organizational variables added significant incremental variance. Results suggest the importance of promoting a moral organization through the words and actions of senior managers and supervisors, independent of formal mechanisms such as codes of conduct.